Incidence of antibiotic resistant pathogenic bacteria in vegetable items sold by local and super shops in Dhaka city - Kabir, Ahmed; Das, Ashish Kumar; Kabir, Md Shahidul (Stamford Journal of Microbiology, 2015)
The present study was carried out to investigate the microbiological quality and antibiotic resistance patterns of pathogenic bacteria isolated from vegetable samples. A total of 14 vegetable samples, 7 from local and 7 from super shops, were randomly collected from different locations of Dhaka city. Concentrations of total heterotrophic bacteria, total coliform, faecal coliform, Pseudomonas spp., Listeria spp. and Staphylococcus aureus were enumerated from each sample by serial dilution and spread plate technique. Presence of Salmonella spp., Shigella spp. and Vibrio spp. were determined by enrichment and selective plating methods. Antibiotic sensitivity patterns of the isolated bacteria were determined using Imipenem (10 ?g), Ceftriaxone (30 ?g), Sulphamethoxazole (25 ?g), Ampicillin (10 ?g), Gentamicin (10 ?g), Aztreonam (30 ?g), Cefuroxime (30 ?g) and Oxacillin (5 ?g) antibiotic discs. The local market vegetables showed higher proportions of E. coli (4/7, 57.14%) but the super shop vegetables showed higher proportions of Pseudomonas spp. (5/7, 71.42%) and Listeria spp. (5/7, 71.42%). Pathogenic bacteria isolated form the super shops showed increased resistance against (5/8, 62.5%) antibiotics tested against the pathogenic bacteria. Contamination of vegetables by a range of pathogenic bacteria in local and super market vegetables is a serious threat to public health if they are consumed raw or unprocessed. Higher antibiotic resistance in pathogens isolated form supermarket vegetables needs to be investigated in order to monitor and control spread of infections with drug resistant bacteria. DOI: http://dx.doi.org/10.3329/sjm.v4i1.22755 Stamford Journal of Microbiology, Vol.4(1) 2014: 13-18